Does high-end housing always have a premium luxury value? A theoretical and numerical study - Hung, Chih-Hsing; Chen, Ming-Chi; Tzang, Shyh-Weir; Cheng, Chung-Chieh (International Journal of Strategic Property Management, 2023)
Using the real options approach, we try to evaluate the luxury value inherent in high-end housing and estimate its premium returns based on the simulation of the model. The key finding of the paper is that the luxury premium from the value of the high-end housing can be identified by the real options model, which is rarely documented in the literature. In addition, the luxury value per unit size of high-end housing can be imputed through the model simulation. Based on the results, we find that the changes of the estimated value per unit size can explain the dynamic housing market behaviour in the recessions and expansions over the business cycle. The luxury value will even become negative during the recession period. In summary, the luxury premiums of high-end housing are higher than those of general housing, but not all highend housing has positive luxury premiums. If sellers and/or builders of high-end housing cannot meet the conditions that maximize the utility of high-end housing buyers, negative returns will accrue from selling high-end housing.